Question about Super Tutor Trigonometry (ESDTRIG) for PC

Ad

Use the formulas

sec(x)=1/cos(x)

csc(x)=1/sin(x)

cot(x)=1/tan(x)

sec(x)=1/cos(x)

csc(x)=1/sin(x)

cot(x)=1/tan(x)

Jul 04, 2015 | Casio FX570MS Scientific Calculator

csc(x)=1/sin(x)

sec(x)=1/cos(x)

csc(x)/sec(x)=(1/sin(x))*(cos(x)=cot(x)

csc(x)*cot(x)/sec(x)=(cot(x))^2=(tan(x))^(-2)

sec(x)=1/cos(x)

csc(x)/sec(x)=(1/sin(x))*(cos(x)=cot(x)

csc(x)*cot(x)/sec(x)=(cot(x))^2=(tan(x))^(-2)

Jul 12, 2014 | Super Tutor Trigonometry (ESDTRIG) for PC

I worked out the algebra leaving out a few simple steps (special binomial products, Pythagorean theorem in trigonometry, definition of secant and co-secant functions). I am inserting the answer as a set of png pictures. However I am not sure how it will look.

Sep 21, 2013 | ValuSoft Bible Collection (10281) for PC

SEC, CSC & COT are the INVERSE of COS, SIN & TAN and are usually require hitting the "2nd F" or "Func" key of the calc to make:

SIN button work as COSEC,

COS button work as SEC

TAN button work as COT

Formulas are below:

sec x = __1 __

cos x

cosec x = __ 1
__

sin x

cot x = __ 1 __ = __cos x__

tan x sin x

Good luck!

Feb 05, 2013 | Sharp EL531 Scientific Calculator

No calculator can have EVERY mathematical function. Very few calculators have the secondary trig functions like cosecant because they're so simple to calculate in other ways. By definition csc(x) is equal to 1/sin(x) and you can calculate it that way. Similarly, calculate sec(x) as 1/cos(x) and cot(x) as 1/tan(x).

Jun 04, 2012 | Texas Instruments TI-36X Scientific...

There are no keys for cosecant, secant, and cotangent. You can calculate those ratios as

csc(x) = 1/sin(x)

sec(x) = 1/cos(x)

cot(x) = 1/tan(x)

Simply calculate the trig ratio on the right and then take its reciprocal.

csc(x) = 1/sin(x)

sec(x) = 1/cos(x)

cot(x) = 1/tan(x)

Simply calculate the trig ratio on the right and then take its reciprocal.

Dec 14, 2010 | Texas Instruments TI-83 Plus Calculator

I shall attempt :D

1) cosec A + cot A = 3

we know that (cot A)^2 + 1 = (cosec A)^2

Hence, (cosec A)^2 - (cot A)^2 = 1

thus, (cosec A + cot A) (cosec A - cot A) = 1

3 (cosec A - cot A) = 1

(cosec A - cot A) = 1/3

(cosec A - cot A) = 1/3

(cosec A + cot A) = 3

Summing them, 2 cosec A = 3 1/3

cosec A = 6 2/3 = 5/3

sin A = 0.15

Thus, cos A = sqrt (1 - (sin A)^2) = 0.989

2) Prove that (1+tan x - sec x)(1 + cot x + cosec x) =2

expand

LHS= 1 + cot x + cosec x + tan x + 1 + tan x cosec x - sec x - sec x cot x - sec x cosec x

We can calculate that

tan x cosec x = sec x (since tan x = sin x / cos x)

sec x cot x = cosec x

so the above is

LHS = 1 + cot x + cosec x + tan x + 1 + sec x - sec x - cosec x - sec x cosec x

LHS = 2 + cot x + tan x - sec x cosec x

LHS = 2 + cos x / sin x + sin x / cos x - 1 / (sin x cos x)

LHS = 2 + [{cos x}^2 + {sin x}^2 - 1] / (sin x cos x)

LHS = 2 (proved)

1) cosec A + cot A = 3

we know that (cot A)^2 + 1 = (cosec A)^2

Hence, (cosec A)^2 - (cot A)^2 = 1

thus, (cosec A + cot A) (cosec A - cot A) = 1

3 (cosec A - cot A) = 1

(cosec A - cot A) = 1/3

(cosec A - cot A) = 1/3

(cosec A + cot A) = 3

Summing them, 2 cosec A = 3 1/3

cosec A = 6 2/3 = 5/3

sin A = 0.15

Thus, cos A = sqrt (1 - (sin A)^2) = 0.989

2) Prove that (1+tan x - sec x)(1 + cot x + cosec x) =2

expand

LHS= 1 + cot x + cosec x + tan x + 1 + tan x cosec x - sec x - sec x cot x - sec x cosec x

We can calculate that

tan x cosec x = sec x (since tan x = sin x / cos x)

sec x cot x = cosec x

so the above is

LHS = 1 + cot x + cosec x + tan x + 1 + sec x - sec x - cosec x - sec x cosec x

LHS = 2 + cot x + tan x - sec x cosec x

LHS = 2 + cos x / sin x + sin x / cos x - 1 / (sin x cos x)

LHS = 2 + [{cos x}^2 + {sin x}^2 - 1] / (sin x cos x)

LHS = 2 (proved)

May 12, 2009 | ValuSoft Bible Collection (10281) for PC

sec^4X- sec^2X = 1/cot^4X + 1/cot^2X

RHS

1/cot^4X + 1/cot^2X

=1/(Cos^4X/Sin^4X) + 1/(Cos^2X/Sin^2X)

=Sin^4X/Cos^4X + Sin^2X/Cos^2X

=Sin^4X/Cos^4X + Cos^2X.Sin^2X/Cos^4X

=Sin^2X/Cos^4(Sin^2X + Cos^2X)

=Sin^2X/Cos^4X

=(1-Cos^2X)/Cos^4X

=1/Cos^4X - Cos^2X/Cos^4X

=1/Cos^4X - 1/Cos^2X

=Sec^4X - Sec^2X

=LHS

RHS

1/cot^4X + 1/cot^2X

=1/(Cos^4X/Sin^4X) + 1/(Cos^2X/Sin^2X)

=Sin^4X/Cos^4X + Sin^2X/Cos^2X

=Sin^4X/Cos^4X + Cos^2X.Sin^2X/Cos^4X

=Sin^2X/Cos^4(Sin^2X + Cos^2X)

=Sin^2X/Cos^4X

=(1-Cos^2X)/Cos^4X

=1/Cos^4X - Cos^2X/Cos^4X

=1/Cos^4X - 1/Cos^2X

=Sec^4X - Sec^2X

=LHS

Feb 02, 2009 | Super Tutor Trigonometry (ESDTRIG) for PC

THIS PROBELM IS TO DIFFICULT SO PLEASE SLOVE THIS PROBELM

Oct 07, 2008 | Computers & Internet

cosec = 1/sin and sec = 1/cos

Oct 03, 2007 | Texas Instruments TI-36 X Solar Calculator

Mar 03, 2013 | Super Tutor Trigonometry (ESDTRIG) for PC

185 people viewed this question

Usually answered in minutes!

×